2008
DOI: 10.1016/j.cognition.2008.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of language experience on the perception of American Sign Language

Abstract: Perception of American Sign Language (ASL) handshape and place of articulation parameters was investigated in three groups of signers: deaf native signers, deaf non-native signers who acquired ASL between the ages of 10 and 18, hearing non-native signers who acquired ASL as a second language between the ages of 10 and 26. Participants were asked to identify and discriminate dynamic synthetic signs on forced choice identification and similarity judgement tasks. No differences were found in identification perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
42
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 39 publications
10
42
0
Order By: Relevance
“…A core question is why we, as well as Newport (1982) and Morford et al (2008), failed to find the classic pattern of categorical perception of minimal handshape contrasts in native signers, whereas the other two prior studies reported finding it for some handshape contrasts Emmorey et al, 2003). Among the potential reasons for the discrepant findings, as discussed earlier, are stimulus and methodology differences.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…A core question is why we, as well as Newport (1982) and Morford et al (2008), failed to find the classic pattern of categorical perception of minimal handshape contrasts in native signers, whereas the other two prior studies reported finding it for some handshape contrasts Emmorey et al, 2003). Among the potential reasons for the discrepant findings, as discussed earlier, are stimulus and methodology differences.…”
Section: Discussionmentioning
confidence: 60%
“…The categorical studies have focused mainly on handshape contrasts, although they have examined a more restricted number and type of location contrasts. The few location contrasts investigated in categorical perception studies have shown neither the categorical patterns seen in speech studies nor any effects of sign language experience Morford et al, 2008;Newport, 1982). Movement contrasts, however, have not been examined yet via categorical perception techniques.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Linked to this possibility are sign perception studies by Best, Mathur, Miranda, and LilloMartin (2010) and Morford et al (2008) that suggest sparser input could discourage categorization and hence lead to maintenance of sensitivity to phonetic contrasts to a higher degree in late than in native signers.…”
Section: Discussionmentioning
confidence: 99%